2009
DOI: 10.1603/029.102.0421
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Ultraviolet Light Affects Immigration Behavior of <I>Ceratothripoides claratris</I> (Thysanoptera: Thripidae)

Abstract: Studies were conducted in tropical greenhouses to elucidate the role of UV light (UV) for the orientation and flight behavior of the thrips Ceratothripoides claratris (Shumsher) (Thysanoptera: Thripidae), an important pest on tomato (Lycopersicum spp.), in the hot and humid tropics of South-East Asia. Four greenhouse types characterized by different combinations of UV-absorbing or -transmitting plastic films and nets on the roof and sidewalls, respectively, were used in these studies. In choice experiments C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…For insects given access to a space with UV radiation and a space from which near-UV radiation was eliminated, many species avoid the latter. Studies have shown reduced incidence of insects such as aphids, whiteflies, and thrips in facilities covered with UVabsorbing film (Costa et al 2002;Nguyen et al 2009;Nonaka and Nagai 1985;Ohta and Kitamura 2006). In addition to vinyl chloride films, products made of highly durable polyolefin films have recently been developed to block near-UV radiation, to prevent infestation inside greenhouses.…”
Section: Control Of Pest Infestation Using Uv-absorbing Filmsmentioning
confidence: 99%
“…For insects given access to a space with UV radiation and a space from which near-UV radiation was eliminated, many species avoid the latter. Studies have shown reduced incidence of insects such as aphids, whiteflies, and thrips in facilities covered with UVabsorbing film (Costa et al 2002;Nguyen et al 2009;Nonaka and Nagai 1985;Ohta and Kitamura 2006). In addition to vinyl chloride films, products made of highly durable polyolefin films have recently been developed to block near-UV radiation, to prevent infestation inside greenhouses.…”
Section: Control Of Pest Infestation Using Uv-absorbing Filmsmentioning
confidence: 99%
“…Initially, insects are excluded from the greenhouse wall due to the lack of UV emission from the inner space of the greenhouse. This effect was well demonstrated by Antignus et al (2001) and Nguyen et al (2009) who monitored lower numbers of whiteflies and thrips, respectively, on sticky traps placed on the outer sidewalls of greenhouses covered with UV-absorbing cladding materials. Hypothetically, a "two-compartment effect" is formed by the photoselective cladding materials: the greenhouse ambient environment has a normal level of UV irradiation, thus representing a UV-rich compartment, while a second UV-deficient compartment is formed within the greenhouse due to UV filtration.…”
Section: Mode Of Action Of Uv-absorbing Greenhouse Cladding Materialsmentioning
confidence: 56%
“…Many insects have two rhodopsins, one with maximum absorption in ultraviolet wavelengths (365 nm) and one with maximum absorption in the green part of the spectrum (540 nm) (Borst, 2009;Matteson, Terry, Ascoli, & Gilbert, 1992). UV component of the light spectrum plays an important role in aspects of insect behavior, including orientation, navigation, feeding, and interaction between the sexes (Mazokhin-Porshnykov, 1969;Nguyen, Borgemeister, Max, & Poehling, 2009;Seliger, Lall, & Biggley, 1994). The involvement of UV rays in the flight behavior of some economically important insect pests has been studied by several workers (Coombe, 1982;Issacs, Willis, & Byrne, 1999;Kring, 1972;Matteson et al, 1992;Moericke, 1955;Mound, 1962;Vaishampayan, Kogan, Waldbauer, & Wooley, 1975;.…”
Section: Uv Vision and Insects Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral manipulation techniques have previously been employed effectively for the control of other classes of pests and pathogens in greenhouses (Raviv & Antignus ; Nguyen et al . ) and to control plant growth without the use of growth regulators (Decoteau et al . ; Rajapakse et al .…”
Section: Discussionmentioning
confidence: 99%